Stacked Denoising Autoencoder network for short-term prediction of electrical Algerian load - Hiba, Chelabi; Tarek, Khadir Mohamed; Belkacem, Chikhaoui (International Conference on Control, Decision and Information Technologies (Online), 2020)
Short-term load forecasting is a topic of considerable interest; it ensures the balance between the production and consumption one day ahead. In this paper, time series models have been developed to provide an efficient forecast for electricity consumption in Algeria using Deep Neural Networks in the form of Stacked Denoising Autoencoder (SDAE) and a regular Multilayer Perceptron (MLP) as a benchmark model. The obtained models are established and evaluated using the hourly temperature and electricity consumption data provided by the Algerian National Electricity and Gas Company (SONELGAZ). Convincing forecasting results for the Algerian national load were found and conclusions drawn.